Education financing through BOS funds at SMA Negeri 1 Tripe Jaya, Gayo Lues Regency - Ismail*, Ismail; Abdul Muis, Zaki; Ali Basyah, Nazaruddin (Riwayat: Educational Journal of History and Humanities, 2023)
This research aims to determine the planning, implementation, and evaluation of education financing through the School Operational Assistance (BOS) funds at SMA Negeri 1 Tripe Jaya in Gayo Lues Regency. The research method employed was descriptive with a qualitative approach. The subjects of the study were the school principal and treasurer of SMA Negeri 1 Tripe Jaya. The object of the study was the education financing through the BOS funds at SMA Negeri 1 Tripe Jaya. Data were collected through interviews, observations, and documentation. They were then analyzed using data reduction techniques, data presentation, and drawing conclusions. The results showed that the planning of education financing through BOS funds at SMA Negeri 1 Tripe Jaya was considered good because it was done carefully and according to plan. A good planning process ensures the effective and efficient use of BOS funds to improve the quality of education. Evaluation of financing through BOS funds provides suggestions for improvements for future planning and implementation.